The relationship between nutrition reading and label use and nutrition knowledge amongst a sample of rural youth studying at a university in South Africa - Nomasonto Xazela; Willie T. Chinyamurindi; Herring Shava (AOSIS, 2019)
Background: Within rural communities, quests for understanding consumer behaviour patterns become key, especially given the challenges that exist in such communities. Furthermore, youth consumers are an important cohort in rural communities in South Africa. Yet little empirical work has been conducted in studying their consumptive habits (usually in favour of youths in urban areas). Aim: This study sought to measure the relationship between nutrition label use and nutrition knowledge amongst a sample of rural youth. This also included ascertaining the roles of demographic variables such as (1) gender and (2) and the number of years in tertiary education in this relationship. Setting: The study was located within a South African rural context using a sample of rural youths. Method: A quantitative study was utilised by means of a self-administered questionnaire, involving 150 youths residing in a rural community located in the Eastern Cape province of South Africa. Inferential statistical analysis was conducted using correlation tests, analysis of variance and linear regression. Results: Three main findings emerged. Firstly, rural youth consumers' nutrition label use had no significant relationship with nutrition knowledge. Secondly, no significant difference existed by gender concerning nutrition knowledge. Finally, the level of education amongst the rural youth consumers had no relationship with aspects of nutrition knowledge. Conclusion: Based on the findings, recommendations are made not only for theory and practice but also for policy in relation to both the rural context and for optimal health.